Effects of the lower energy and pulse stacking in carbon dioxide laser skin treatment: an objective analysis using second harmonic generation - Motta,Marcos Matias (2021)
ABSTRACT Purpose To evaluate the effect of fractional carbon dioxide (CO2) laser treatment using lower power associated with pulse stacking within collagen fibers, using second harmonic generation microscopy and computerized image analysis. Methods Twenty male Wistar rats aging eight weeks were used. Each treatment area received a single-pass CO2 fractional laser with different parameters. The 20 animals were divided into two groups and euthanized after 30 and 60 days. Second harmonic generation images were obtained and program ImageJ was utilized to evaluate the collagen organization within all areas. Collagen anisotropy, entropy and optical density were quantified. Results Increased anisotropy over time was observed in all four areas, but only reached statistical significance (p = 0.0305) when the mildest parameters were used (area four). Entropy decreased over time in all areas, but without significance(p = 0.1779) in area four. Density showed an overtime increase only in area four, but no statistical significance was reached (p = 0.6534). Conclusions When combined, the results obtained in this study regarding anisotropy, entropy and density tend to demonstrate that it is possible to achieve collagen remodeling with the use of lower power levels associated with stacked pulses.